Offloading information to an external store increases false recall. - Lu, Xinyi; Kelly, Megan O.; Risko, Evan F. (Elsevier, 2020)
Offloading to-be-remembered information is a ubiquitous memory strategy, yet in relying on external memory stores, our ability to recall from internal memory is often diminished. In the present investigation, we examine how offloading impacts true and false recall. Across three experiments, participants studied and wrote down word lists that were each strongly associated with an unstudied critical word. Recall in the Offloading condition (i.e., when they were told that they would have access to their written lists during recall) was contrasted with a No-Offloading condition (i.e., when they were told that they would not have access to their written lists during recall). We found that offloading decreased true recall of presented words while increasing false recall for unpresented critical words. Results are discussed in terms of offloading’s differential effects on the formation of gist and verbatim traces during encoding.
This is the peer reviewed version of the following article: Lu, X., Kelly, M. O, & Risko, E. F. (2020). Offloading information to an external store increases false recall. Cognition, 205, 104428., which has been published in final form at https://doi.org/10.1016/j.cognition.2020.104428. ©2020. This manuscript version is made available under the CC-BY NC-ND 4.0 license https://creativecommons.org/licenses/bync-nd/4.0/
Keywords: memory; cognitive offloading; false memory; recall